Xây dựng phương pháp phát hiện Paracetamol trộn trái phép trong chế phẩm Đông dược bằng sắc ký lớp mỏng kết hợp tán xạ Raman tăng cường bề mặt (TLC-SERS) / Đào Thị Cẩm Minh, Lê Văn Vũ, Nguyễn Thị Kiều Anh, Phạm Thị Thanh Hà - Đào, Thị Cẩm Minh
A novel TLC-SERS (thin-layer chromatography combined with surface enhanced Raman spectroscopy) method was developed for detection of adulterated paracetamol in herbal products. TLC separation was performed on methanol extracts from the herbal products. Nano silver colloid prepared in water was introduced on the TLC plate at the position equivalent to paracetamol before SERS spectrum was recorded. Type and concentration of nano silver colloid was investigated, and typical Raman shifts on the SERS spectrum of paracetamol were selected for the identification. The analytical method was validated for specificity and limit of quantitation. Fourteen herbal products were analyzed, Of these products, three were detected with paracetamol adulteration. This is the first study in Vietnam using TLC-SERS in quality control of herbal products.